Analisis Kualitas Tes Bahasa Arab di Indonesia: Studi Systematic Literature Review tentang Validitas, Reliabilitas, Tingkat Kesukaran, dan Daya Beda - Ulya Nur Alim; Syahrul Syahrul; Luís Miguel Oliveira de Barros Cardoso; Suryadi Ishak; Andi Asrifan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
Evaluation in Arabic language learning is essential to measure students' achievement; however, the quality of tests used in Indonesia still requires improvement. This study employed the Systematic Literature Review (SLR) method to analyze the validity, reliability, difficulty level, and discrimination power of Arabic test items, based on a synthesis of six articles indexed in SINTA and Scopus, published between 2019 and 2024. This SLR approach offers a new contribution by systematically revealing national trends and gaps in item quality, which have not been comprehensively analyzed in previous studies. The findings show that on average, 66% of the items were valid, and most tests demonstrated very high reliability (≥ 0.85), although some tests had low reliability (0.54). The distribution of difficulty levels was imbalanced, with 50.83% of items being too easy and only 7.67% classified as difficult, deviating from the ideal distribution. Additionally, 34% of the items exhibited low discrimination power, reducing the effectiveness of assessments in distinguishing students' abilities. These imbalances can lead to biased evaluations and hinder students' competency development. The practical implications of this study include the importance of teacher training in item analysis, the application of Bloom's Taxonomy to balance item difficulty levels, and the development of a standardized, data-driven item bank. The main contribution of this research is to provide empirical foundations for improving Arabic language assessment policies in Indonesia and to propose a more accurate and fair evidence-based evaluation approach.